2006
DOI: 10.1007/s00204-006-0160-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of metal transporters by dietary iron, and the relationship between body iron levels and cadmium uptake

Abstract: Iron (Fe) plays essential roles in biological processes, whereas cadmium (Cd) is a toxic and non-essential metal. Two metal transporters, divalent metal transporter 1 (DMT1) and metal transporter protein 1 (MTP1), are responsible for Fe transport in mammals. Here, we studied the effect of dietary Fe on the expression of these metal transporters in peripheral tissues, and the uptake by these tissues of Cd. Mice were fed an Fe-sufficient (FeS: 120 mg Fe/kg) or Fe-deficient (FeD: 2-6 mg Fe/kg) diet for 4 weeks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 34 publications
1
43
1
2
Order By: Relevance
“…This up-regulation in irondeficient status has been observed in rats, [2][3][4] mice, 6) and humans. 5) Kim et al 6) have reported that the expression of DMT1 mRNA was 65 times higher in iron-deficient mice than in the controls. The up-regulation of DMT1 mRNA in rats has been shown by RT-PCR and northern blotting, and there have been several quantitative analyses.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…This up-regulation in irondeficient status has been observed in rats, [2][3][4] mice, 6) and humans. 5) Kim et al 6) have reported that the expression of DMT1 mRNA was 65 times higher in iron-deficient mice than in the controls. The up-regulation of DMT1 mRNA in rats has been shown by RT-PCR and northern blotting, and there have been several quantitative analyses.…”
mentioning
confidence: 66%
“…Iron deficiency is well known to result in increased iron absorption in the small intestine, and increased expression of divalent metal transporter 1 (DMT1), which is located in the intestinal brush border, has also been observed. [2][3][4][5][6] DMT1 is the only non-heme iron transporter on the intestinal mucosal surface, according to results from global knockout mice. 7) On the other hand, intestinal iron absorption is inhibited for several days by excess iron loading, and this response to excess iron is called ''mucosal block.…”
mentioning
confidence: 99%
“…If Cd accumulation levels in testes or cauda epididymis are different by injection timing, transporters like ZIP8, ZIP14 and DMT1 (Kim et al, 2007;Girijashanker et al, 2008), which involve in Cd transport into these organs, may contribute to the diurnal variation. Induction level of metallothionein, a well known and important defense factor against Cd toxicity, should also be considered (Siu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several candidate transporters and channels involved in cadmium uptake in mammalian cells have been proposed: calcium channel (Leslie et al, 2006), calcium transporter (Min et al, 2008), iron transporter (Ryu et al, 2004;Kim et al, 2007;Bannon et al, 2003), zinc transporter (Dalton et al, 2005;He et al, 2006;Wang et al, 2007;Liu et al, 2008) and magnesium transporter (Martine et al, 2008). However, the role of each transport system in cadmium uptake remains still elusive.…”
Section: Introductionmentioning
confidence: 98%